Application of Adhikarana and Yoga Tantrayukthi in Ashtanga Sangraha Sutrasthana Based on Neelamegha’s Definition - Krishna K (International Journal of Ayurveda and Pharma Research, 2025)
Tantrayukthi is defined as the methodology and technique which enable one to compare and interpret scientific treatises correctly and intelligently. Only through the study and contextual application of these techniques, one can comprehend Ayurvedic principles completely. Ashtanga Sangraha of Acharya Vagbhata is an ancient authoritative text on Ayurveda, studied since many centuries by students, scholars and practitioners of Indian medicine. Because of its archaic style of composition and terse language, certain amount of difficulty is being experienced. Since all the Tantrayukthis cannot be done as a single work, this study is an attempt to find out the application of Adhikarana and Yoga Tantrayukthi in Asthanga Sangraha Sutrasthana based on Neelamegha’s definition.